Development of Reading Literacy Application System using Extreme Programming Method - Bahres, Salim Bin Sulaiman; Subhiyakto, Egia Rosi (Sistemasi: Jurnal Sistem Informasi, 2024)
Along with the advancement of technology, educational media is experiencing progress. Traditional learning methods are shifting and being replaced by technology-based learning. One crucial aspect of technological advancement is the ability to comprehend written text. The lack of interest in reading can have adverse effects, such as being susceptible to fake news without clear sources. The reading interest in Indonesia is notably low. According to data from the Programme for International Student Assessment (PISA), Indonesia ranks 74th out of 79 countries in terms of reading literacy skills. The development of a literacy reading website can be a solution to address this issue, particularly in enhancing an individual's reading interest and skills. In this research, the development of the literacy reading website employs the Extreme Programming development method as it considered highly effective in meeting project requirements that demand swift execution and quick adaptation to change. The objective of this study is to create a literacy reading website with a narrative and e-learning concept, featuring literacy readings and quizzes to support the improvement of reading skills. The results indicate that the literacy reading website functions well and can be effectively utilized in the reading skills training process, validated through functional testing using the black-box testing method with 100% results.